Orthodontic considerations and timing selection for patients with stage Ⅳ periodontitis - PENG Yan, ZHANG Chi, GAO Li, LI Xiting, ZHAO Chuanjiang (Kouqiang yixue)
Patients suffering from stage Ⅳ periodontitis manifest substantial alveolar bone destruction and pronounced tooth loss, frequently accompanied by masticatory dysfunction, occlusal disorder and tooth displacement or torsion. Standard periodontal interventions alone are insufficient to stabilize the condition, address masticatory dysfunction, and enhance patients’ quality of life. Hence, intricate reconstructive and interdisciplinary regimens, encompassing orthodontic treatment, are often indispensable. Orthodontic therapy can optimize the masticatory function and esthetic appearance of patients, and promote periodontal well-being. However, individuals with stage Ⅳ periodontitis present with inadequate periodontal support tissue and a heightened risk profile, rendering their orthodontic management a considerable clinical challenge. This article reviews the orthodontic considerations and optimal timing for intervention in patients with stage Ⅳ periodontitis and presents a representative case of combined periodontal-orthodontic-orthognathic treatment for periodontitis(stage Ⅳ, grade C), in order to provide reference for periodontists and orthodontists.